REGULATION ASPECT OF LEARNERS' LANGUAGE LEARNING STYLE IN DIFFERENTIATED ESP INSTRUCTION - Oksana Synekop (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
This study aims to investigate the issue of regulation aspect of learner's language learning style in differentiated instruction of English for Specific Purposes (ESP) at technical universities. In particular, we defined and characterised the self-regulation levels of information technology (IT) students; outlined recommendations for improvement of students' regulation while developing listening, speaking, reading and writing skills. To achieve that purpose we used mixed research methods in our study which involved 382 third- and fourth-year IT students. To collect the data, "Self-regulation Style of Learning Activities" questionnaire developed by Morosanova and Bondarenko (2015), was used. As shown by the survey, most learners had a medium level of self-regulation, smaller number of students had a high level of self-regulation, and only some of them had a low level of self-regulation, which implies that students need to develop their regulation skill. Using the descriptors suggested by Morosanova and Bondarenko (2015), we defined students' self-regulation levels in ESP instruction. To enhance the level of self-regulation, share-regulation and co-regulation in ESP learning the recommendations were given. In particular, since learning can be conducted individually, in pairs, teams and groups, various specifics of students' regulation in ESP study was reflected in checklists for self-regulation, socially shared regulation and co-regulation. For creating the checklists, the phases of Zimmerman (2003) model and cognition, metacognition, motivation, emotion, and behaviour regulation areas were used. Finally, recommendations were suggested to ESP teachers for improvement of learners' regulation while developing listening, speaking, reading and writing skills in differentiated ESP instruction.